1975
DOI: 10.1007/bf00421012
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of haloperidol and chlorpromazine in terms of clinical effects and therapeutic reversal with benztropine in schizophrenia. Theoretical implications for potency differences among neuroleptics

Abstract: In a double-blind, cross-over study, the comparative therapeutic effects of 6-week courses of two prototypic neuroleptics--haloperidol and chlorpromazine--and the reversal of those effects with benztropine were investigated in a group of 18 schizophrenics. Periodic measurements were made for 32 dimensions of psychopathology, social participation, span of attention, sleeplessness, pulse rate and neurological side effects. The results showed that haloperidol was generally a more effective drug over the period st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 15 publications
0
43
0
1
Order By: Relevance
“…All but one of the statistically significant findings indicated that AP inter ventions had been countertherapeutic and involved clinical parameters that would be recognized as being characteristic of schizophrenic psychosis and its response to neuroleptic treatment (4,22,23).…”
Section: Countertherapeutic a P Effects Prognostic Classification Anmentioning
confidence: 99%
See 1 more Smart Citation
“…All but one of the statistically significant findings indicated that AP inter ventions had been countertherapeutic and involved clinical parameters that would be recognized as being characteristic of schizophrenic psychosis and its response to neuroleptic treatment (4,22,23).…”
Section: Countertherapeutic a P Effects Prognostic Classification Anmentioning
confidence: 99%
“…In studies II and III, a more detailed Psychopathology Rating Schedule was employed that included the previous items and used comparable criteria (22). A team o f specially trained raters, including psychologists, social workers and psychiatric nurses, gave the ratings (once a week in study 1 and once every other week in studies II and III) on the basis o f a semistructured clinical interview, usually lasting an hour or more.…”
Section: Measurementsmentioning
confidence: 99%
“…The PANSS, which includes a positive scale, a negative scale and a general psychopathology scale, is based on 18 items of the Brief Psychiatric Rating Scale (BPRS; Beller and Overall 1984) and 12 items of the Psychopathology Rating Schedule (PRS; Singh and Kay 1975).…”
Section: Introductionmentioning
confidence: 99%
“…While antiparkinsonian drugs, by decreasing ab sorption and consequently serum levels, may interfere with the therapeutic ac tion of neuroleptics (Singh and Ray, 1975;Rivera-Calimlim, 1976), tricyclic antidepressants, by increasing serum levels, enhance their pharmacological ef fects. Nevertheless, simultaneous administration of an antiparkinsonian drug and a tricyclic antidepressant may intensify the anticholinergic action, of the neuro leptic such that confusional state, bladder atonia, or paralytic ileus may occur.…”
Section: Neurolepticsmentioning
confidence: 99%